COLLABORATIVE WRITING ON GOOGLE DOCS: PERCEPTION OF ELEVENTH GRADE STUDENTS’ DESCRIPTIVE PARAGRAPH IN PGRI VOCATIONAL HIGH SCHOOL 1 PALEMBANG - Pramestry Yonanda; Herlina Herlina; M. Ali Akbar Zam (Universitas PGRI Palembang, 2024)
The researcher's experience when conducting field experience practice (PPL) at PGRI Vocational High School 1 Palembang served as inspiration for this research. The researcher found that students experience problems when they want to write, including due to a lack of practice, a weakness in using correct grammar, and a lack of motivation. Therefore, in this study, the researcher used a collaborative learning method using Google Docs. The aimed of this research is to implement the use of Google Docs with grade XI students in collaborative writing of descriptive paragraphs and to determine students' perceptions of the use of Google Docs in collaborative writing of descriptive paragraphs. This research used the descriptive-qualitative method with a sample of 32 students. Data were collected through observation, questionnaires, and documentation. Looking at the results of students' implementation of the use of Google Docs in collaborative writing of descriptive paragraphs, it is said to be successful because students are able to exceed the KKM score of 75. For students' perceptions, it can be said to be a positive perception because most of them strongly agreed and agreed on the 20 questionnaire statements that researchers distributed; this means that students were able to write the text better.